Structural, electronic, and vibrational properties of (4,4) picotube crystals - Machon, Maria; Reich, Stephanie; Maultzsch, Janina; Okudera, H; Simon, A; Herges, Rainer; Thomsen, Christian (Physical Review B, 2005)
The picotube molecule is a highly symmetric hydrocarbon, closely related to a very short (4,4) carbon nanotube. We present a thorough experimental and theoretical study of the physical properties of picotube crystals. In x-ray diffraction experiments we find the picotube molecules to display D-2d symmetry. We identify the most intense Raman peaks as A(1) modes with polarization-dependent Raman measurements. Ab initio calculations of the structural, electronic, and vibrational properties of picotubes are in excellent agreement with our experiments. We assign the measured vibrations to displacement eigenvectors including those analogous to the nanotube high-energy mode, the D mode, and the radial-breathing mode.